Answer:
n = -15 and m = -3
Step-by-step explanation:
To solve the given system of equation, we will follow the steps below:
n = 5m ----------------------------------------------------------------------------(1)
n = [tex]\frac{2}{3} m -13[/tex] ---------------------------------------------------------------------(2)
substitute for n= 5m in equation (2)
5m = [tex]\frac{2}{3} m -13[/tex]
subtract [tex]\frac{2}{3} m[/tex] from both-side of the equation
5m - [tex]\frac{2}{3} m[/tex] = [tex]\frac{2}{3} m[/tex] - [tex]\frac{2}{3} m -13[/tex]
At the right-hand side of the equation [tex]\frac{2}{3} m[/tex] will cancel-out leaving us with just -13
5m - [tex]\frac{2}{3} m[/tex] = -13
[tex]\frac{15m - 2m }{3}[/tex] = -13
[tex]\frac{13m}{3}[/tex] = -13
multiply both-side of the equation by 3
3 × [tex]\frac{13m}{3}[/tex] = -13 × 3
At the left-hand side of the equation 3 will cancel-out 3 leaving is with just 13m
13m = -39
Divide both-side of the equation by 13
13m/13 = -39/13
m = -3
substitute m = -3 in equation (1)
n = 5m
n = 5 (-3)
n = -15
Therefore, n = -15 and m = -3